WNT5A is transported via lipoprotein particles in the cerebrospinal fluid to regulate hindbrain morphogenesis - Kaiser, Karol; Gyllborg, Daniel; Procházka, Jan; Salašová, Alena; Kompaníková, Petra; Molina, Francisco Lamus; Laguna-Goya, Rocio; Radaszkiewicz, Tomasz; Harnoš, Jakub; Procházková, Michaela; Potěšil, David; Barker, Roger A; et al. (Nature communications, 2019)
WNTs are lipid-modified proteins that control multiple functions in development and disease via short- and long-range signaling. However, it is unclear how these hydrophobic molecules spread over long distances in the mammalian brain. Here we show that WNT5A is produced by the choroid plexus (ChP) of the developing hindbrain, but not the telencephalon, in both mouse and human. Since the ChP produces and secretes the cerebrospinal fluid (CSF), we examine the presence of WNT5A in the CSF and find that it is associated with lipoprotein particles rather than exosomes. Moreover, since the CSF flows along the apical surface of hindbrain progenitors not expressing Wnt5a, we examined whether deletion of Wnt5a in the ChP controls their function and find that cerebellar morphogenesis is impaired. Our study thus identifies the CSF as a route and lipoprotein particles as a vehicle for long-range transport of biologically active WNT in the central nervous system.
Keywords: signální transdukce; Signal Transduction; Humans; protein Wnt 5a; rombencefalon; Lipoproteins; Female; Wnt-5a Protein; lidé; zvířata; Choroid Plexus; Morphogenesis; Mice, Inbred ICR; morfogeneze; biologický transport; ženské pohlaví; Rhombencephalon; Male; plexus chorioideus; Animals; lipoproteiny; myši inbrední ICR; mužské pohlaví; Biological Transport